MADURA’S POSTPARTUM HERBAL MEDICINE IN THE EYES OF MOTHER IN POSTPARTUM PERIOD - Sri Yunita Suraida Salat; Ahmaniyah Ahmaniyah; Emdat Suprayitno (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
Currently the development of modern medicine is happening, the people in Sumenep persist in using and consuming Jamu (Indonesian traditional herbal medicine) to prevent and to cure diseases, in the process of pregnancy, childbirth and the postpartum period. This habit was inherited from their ancestors. This study aimed to describe views and opinions of postpartum mothers on the puerperal herbal medicine that they consumed during the postpartum period. This study design was qualitative study with a phenomenological approach with total participants were 20 postpartum mothers and their families and 2 postpartum herbal medicine makers. Data were collected by direct observation through in-depth interviews. The results showed 5 themes describing the dynamics of the Madurese traditional herbal medicine in the viewpoint of post-partum mothers, namely their reasons for consuming postpartum traditional herbal medicine, the form of the herbal traditional medicine consumed, their knowledge of postpartum herbal medicine, the benefits of postpartum traditional herbal medicine, and the mother's desire to consume the puerperal herbal medicine in the future. It can be concluded that there was different viewpoint that described by postpartum women about consuming postpartum herbal medicine. In general, they found that postpartum herbal medicine had benefits directly in the recovery process of the postpartum period and increasing breast milk production